Using relative gas diffusivity to highlight soil compaction issues with possible effects on N efficiency in grain corn production, southern Quebec, Canada - Jean Caron; Vincent Grégoire; Alain N. Rousseau; Jacynthe Dessureault Rompre; Gabriel Deslauriers; Diane Bulot; Josselin Bontemps; Didier Vieux; Thiago Gumiere; Hossein Bonakdari (Vadose Zone Journal)
Abstract It has long been suggested that soil compaction indices should be monitored as part of a routine soil management program. Moreover, in addition to properties related to storage of gases and fluid within a bulk volume (i.e., bulk density [BD] and air porosity [θa]), some authors have suggested that properties linked to fluid and gas exchanges such as gas diffusion and hydraulic conductivity should be used to assess the physical health of soils. Given the risk of severe compaction due to the increasing size of farm equipment and the lack of long rotation in cash crop production, data on soil storage and exchange properties need to be collected. The objective of this study was to assess the physical soil health of the top 30 cm of 18 southern Quebec corn fields using a set of indicators. The data were also used to determine crop response to nitrogen fertilization. The results showed that over 93% of the corn fields had a relative gas diffusivity (Ds/Do) below the 0.03 threshold at both 15‐ and 30‐cm depth, suggesting substantial crop growth limitations. They also showed that around 40% of the soils had subsurface drainage problems linked to a low saturated hydraulic conductivity (49% at 15 cm and 47% at 30 cm lower than 0.001 cm s−1). The levels of relative gas diffusivity were low, not only limiting crop growth but also likely reducing nitrogen efficiency through increasing risk of denitrification. Moreover, the results suggest that in some fields, high yields can be achieved with as little as 60 and up to 215 kg of nitrogen per hectare, and that slow‐draining soils will have a very poor response to N fertilization, leading to lower net revenues and nitrogen losses. Overall, the findings suggest that appropriate soil conservation and water management practices based on soil physical health criteria like relative gas diffusivity and hydraulic conductivity must be implemented to maintain or improve soil productivity and health in the face of climate change.